Jian-Ti-Kang-Yi decoction alleviates poly(I:C)-induced pneumonia by inhibiting inflammatory response, reducing oxidative stress, and modulating host metabolism - Cui, Huantian; Wang, Yuming; Yu, Bolun; Wu, Yulin; Zhang, Gaijun; Guo, Junli; Luo, Junyu; Li, Qin; Li, Xiaojuan; He, Wenju; Wen, Weibo; Liao, Jiabao; et al. (Frontiers in Pharmacology, 2022)
Jian-Ti-Kang-Yi decoction (JTKY) is widely used in the treatment of COVID-19. However, the protective mechanisms of JTKY against pneumonia remain unknown. In this study, polyinosinic-polycytidylic acid (poly(I:C)), a mimic of viral dsRNA, was used to induce pneumonia in mice; the therapeutic effects of JTKY on poly(I:C)-induced pneumonia model mice were evaluated. In addition, the anti-inflammatory and anti-oxidative potentials of JTKY were also investigated. Lastly, the metabolic regulatory effects of JTKY in poly(I:C)-induced pneumonia model mice were studied using untargeted metabolomics. Our results showed that JTKY treatment decreased the wet-to-dry ratio in the lung tissue, total protein concentration, and total cell count of the bronchoalveolar lavage fluid (BALF). Hematoxylin and Eosin (HE) and Masson staining indicated that the JTKY treatment alleviated the pathological changes and decreased the fibrotic contents in the lungs. JTKY treatment also decreased the expression of pro-inflammatory cytokines [interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-α)] and increased the levels of immunomodulatory cytokines (IL-4 and IL-10) in the BALF and serum. Flow cytometry analysis showed that the JTKY treatment lowered the ratio of CD86+/CD206+ macrophages in the BALF, decreased inducible nitric oxide synthase (iNOS) level, and increased arginase 1 (Arg-1) level in lung. JTKY also lowered CD11b+Ly6G+ neutrophils in BALF and decreased myeloperoxidase (MPO) activity in lung. Moreover, it also elevated superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities and decreased methane dicarboxylic aldehyde (MDA) level in lung. Untargeted metabolomic analysis showed that the JTKY treatment could affect 19 metabolites in lung, such as L-adrenaline, L-asparagine, ornithine, and alpha-ketoglutaric acid. These metabolites are associated with the synthesis and degradation of ketone bodies, butanoate, alanine, aspartate, and glutamate metabolism, and tricarboxylic acid (TCA) cycle processes. In conclusion, our study demonstrated that treatment with JTKY ameliorated poly(I:C)-induced pneumonia. The mechanism of action of JTKY may be associated with the inhibition of the inflammatory response, the reduction of oxidative stress, and the regulation of the synthesis and degradation of ketone bodies, TCA cycle, and metabolism of alanine, aspartate, glutamate, and butanoate processes in lung.